Efficacy of low dose magnesium sulphate regime and Pritchard’s regime in controlling of eclamptic convulsion and prevention of recurrence - Karande, Suryaprakash Jagdevappa; Shah, Archana S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is defined as the onset of convulsions or coma during pregnancy or in post-partum period in a patient who has signs and symptoms of pre-eclampsia. It is life threatening emergency that continues to be a major cause of serious maternal morbidity and mortality also along with high perinatal mortality and morbidity. The present study undertaken to determine the efficacy of low dose magnesium sulphate regime and Pritchard’s regime in controlling eclamptic convulsion and prevention of recurrence of convulsion. Methods: Out of total 60 patients enrolled in the study; 30 were given low dose magnesium sulphate regime and remaining 30 with Pritchard’s regime. Selection of patients was done with simple random sampling. Relevant history was obtained from the patient, if conscious, or from the relatives. Through clinical examination was done and blood samples were collected for investigations after securing IV line. Results: There was insignificant difference regarding type of eclampsia in both groups. Recurrence of convulsion in Pritchard’s regime group was 6.67% and in Low dose regime group found to be 10% but this was statistically insignificant. Total dose of magnesium sulphate required in Low dose regime group was less than that required for Pritchard’s regime. Conclusions: Low dose magnesium sulphate Regime proved equally effective as that of Pritchard’s regime in control of convulsion in spite of less amount of drug and comparatively low serum magnesium levels and hence there is hardly any fear of intoxicator.